Scientific data mining a practical perspective - Kamath, Chandrika (Society for Industrial and Applied Mathematics, 2009)
Chandrika Kamath describes how techniques from the multi-disciplinary field of data mining can be used to address the modern problem of data overload in science and engineering domains. Starting with a survey of analysis problems in different applications, it identifies the common themes across these domains.